1991
DOI: 10.1002/j.1460-2075.1991.tb07709.x
|View full text |Cite
|
Sign up to set email alerts
|

A pause site for RNA polymerase II is associated with termination of transcription.

Abstract: Termination of transcription by RNA polymerase II has been postulated to involve a pausing process. We have identified such a pause signal, 350 bp into the 3′ flanking region of the human alpha 2 globin gene at a position where termination is thought to occur. We show that this pause signal enhances the utilization of an upstream poly(A) site which is otherwise out‐competed by a stronger downstream poly(A) site. We also demonstrate that the pause site rescues a poly(A) site that is inactive due to its location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 41 publications
5
92
0
Order By: Relevance
“…Results from a number of laboratories have shown that when two polyadenylation sites are duplicated and separated by relatively short distances, the upstream polyadenylation site is used preferentially (19,28,(45)(46)(47)(48). However, one study showed that for duplicated poly(A) sites, a stronger downstream one could outcompete a weaker upstream one when less than 400 bp away (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a number of laboratories have shown that when two polyadenylation sites are duplicated and separated by relatively short distances, the upstream polyadenylation site is used preferentially (19,28,(45)(46)(47)(48). However, one study showed that for duplicated poly(A) sites, a stronger downstream one could outcompete a weaker upstream one when less than 400 bp away (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, one study showed that for duplicated poly(A) sites, a stronger downstream one could outcompete a weaker upstream one when less than 400 bp away (19). In those instances where RNA levels were measured, there was no significant change in mRNA amounts produced by constructs with multiple signals (28,45,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increased RNAPII density at the 39-end may reflect pausing of RNAPII that precedes termination. Indeed, transcription pause sites located downstream from poly(A) sites appear to play a role in RNAPII 39-end processing and termination, at least in mammalian genes, such as a-globin and g-globin genes (Enriquez-Harris et al 1991;Plant et al 2005). A G-rich sequence (MAZ element: G 5 AG 5 ) was identified downstream from the poly(A) site of the liver-specific C2 complement gene (Ashfield et al 1994;Proudfoot 1999, 2000).…”
Section: Pausing the Polymerase: Another Factor In Rnapii Terminationmentioning
confidence: 99%
“…As mature transcripts are generally mapped by cDNA cloning, the extent of most primary transcription units is unknown. Nuclear run-on (NRO) analysis, which measures polymerase density, has generally been applied only to single genes and their immediate flanking regions (Hagenbuchle et al 1984;Ashfield et al 1991;Enriquez-Harris et al 1991). Therefore, transcription of complete intergenic regions in gene loci has not been investigated.…”
mentioning
confidence: 99%